Cecal Schwannoma: A Rare Cause of Gastrointestinal Bleeding in a Young Woman with Review of Literature. (15th June 2011) - Kanneganti, Kalyan; Patel, Harish; Niazi, Masooma; Kumbum, Kavitha; Balar, Bhavna
Abstract : Schwannomas are rare mesenchymal tumors of the gastrointestinal tract. Occurrence of these tumors is more common in the stomach than in the large intestine. These tumors usually present as polypoidal intraluminal lesions and based on their location can present with rectal bleeding, colonic obstruction, and abdominal pain or defecation disorders. We present a case of a thirty-five-year-old woman who presented with abdominal pain and melena. Patient was diagnosed with a nonobstructing superficially ulcerated mass in the cecum on colonoscopy and required right hemicolectomy. A very rare pathological diagnosis of cecal schwannoma was made postoperatively.